Revealing of sexually transmitted diseases to sexual partners: a bioethical dilemma? - Carvalho, Fernanda T.; Rocha, Kátia B.; D’Elia, Paula; Fontoura, Vaneza A. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
This paper focuses on the ethical point of view of health professionals concerning to revealing diagnosis to sexual partners of patients with Sexually Transmitted Infections (IST). This is a descriptive study in which a fictitious case involving confidentiality was presented to two Bioethics expertiseand three patients who searched for health care in a Genital Health Clinic. The participants were questioned on how a healthcare professional should be have when facing this situation and the answers were recorded to further contend analysis. The participants interviews were very rich and, in somepoints, divergent. This paper emphasizes that ethics and bioethics are important tools for helping health professionals who work with STI. The authors reinforce individual counseling as an important intervention to help the patient to inform his diagnosis to his partner.